The impact of sustained malaria control in the Loreto region of Peru: a retrospective, observational, spatially-varying interrupted time series analysis of the PAMAFRO program - Janko, M.M.; Recalde-Coronel, G.C.; Damasceno, C.P.; Salmón-Mulanovich, G.; Barbieri, A.F.; Lescano, A.G.; Zaitchik, B.F.; Pan, W.K. (Elsevier, 2023)
Although malaria control investments worldwide have resulted in dramatic declines in transmission since 2000, progress has stalled. In the Amazon, malaria resurgence has followed withdrawal of Global Fund support of the Project for Malaria Control in Andean Border Areas (PAMAFRO). We estimate intervention-specific and spatially-explicit effects of the PAMAFRO program on malaria incidence across the Loreto region of Peru, and consider the influence of the environmental risk factors in the presence of interventions.
Keywords: Malaria; PAMAFRO; Climate; Interrupted time series; Spatially-varying coefficients; Loreto; https://purl.org/pe-repo/ocde/ford#3.01.05